Therapy escape mechanisms in the malignant prostate. (December 2015) - Santer, Frédéric R.; Erb, Holger H.H.; McNeill, Rhiannon V.
Abstract: Androgen receptor (AR) is the main target for prostate cancer therapy. Clinical approaches for AR inactivation include chemical castration, inhibition of androgen synthesis and AR antagonists (anti-androgens). However, treatment resistance occurs for which an important number of therapy escape mechanisms have been identified. Herein, we summarise the current knowledge of molecular mechanisms underlying therapy resistance in prostate cancer. Moreover, the tumour escape mechanisms are arranged into the concepts of target modification, bypass signalling, histologic transformation, cancer stem cells and miscellaneous mechanisms. This may help researchers to compare and understand same or similar concepts of therapy resistance in prostate cancer and other cancer types.